Unusual types of extended defects in synthetic high pressure–high temperature diamonds. Issue 47 (16th November 2018) - Shiryaev, Andrey A.; Zolotov, Denis A.; Suprun, Olena M.; Ivakhnenko, Sergei A.; Averin, Alexey A.; Buzmakov, Alexey V.; Lysakovskyi, Valentin V.; Dyachkova, Irina G.; Asadchikov, Victor E.
Abstract : Side view of a HPHT diamond with unusual cone-like defects and the high magnification image of the defect. Abstract : New unusual types of extended defects resembling bunches of divergent dislocations are observed in high quality synthetic HPHT single crystal diamonds grown at the lowest possible PT-conditions. Thorough characterisation of the samples by X-ray topotomography, optical microscopy and vibrational spectroscopy allowed the conclusion that these defects are related to dislocations decorated by oxide inclusions. An unusual feature of the defects is their origin: small-angle grain boundaries formed during growth instabilities. Although similar defects were observed in some isostructural materials, their presence in diamonds was not reported earlier.